ANALISIS PERBANDINGAN STRUKTUR DAN BIAYA ANTARA KONSTRUKSI BAJA DAN BETON BERTULANG (Studi Kasus Gedung Pusat Promosi dan Pemasaran PPIK Kota Tasikmalaya) - Maskur, Atep; Saepudin, Uu; Aliya Syariati, Lutfi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Building is a physical form of work that functions as a place to live, for religious, social, cultural activities, as well as special activities. In building construction the types of structures that can be used steel construction and reinforced concrete structures. The two structures differ in terms of nature, material, method of implementation and most importantly in terms of strength and cost. The purpose of this research is to plan reinforced concrete structures using the Etabs program to determine the dimensions of columns and beams, as well as to analyze the cost of reinforced concrete columns and beams. As a comparison to the structure and cost of elements columns and beams steel construction, is this alternative more efficient and economical or vice versa. Research using comparative method. The comparative method is research that is intended to determine the level of difference a variable from two different groups.The results of the research show that a comparison of structures based on the strength to carry the same load on column and beam elements is obtained for existing steel construction K1-H400, K2-H300, B1-WF500, B2-WF450, B3-WF350, B4-WF300, B5-WF200, B6-WF250, B7-WF150, B8-WF400. while for reinforced concrete the planning results using the Etabs program obtained K1 50x50cm, K2 40x40cm, B1 30x60cm, B2 25x50cm, BA 20x40cm. Cost comparison between steel construction and reinforced concrete for column and beam elements with the existing price of steel construction Rp. 2,491,416,316. while the price of reinforced concrete structures is Rp. 789,569,564. the cost of reinforced concrete structures is cheaper than steel construction with a difference in costs of Rp. 1,701,846,752 or a percentage of 68.3 %